Vascular Smooth Muscle Cells Contribute to Atherosclerosis Immunity - Hu, Desheng; Yin, Changjun; Luo, Shanshan; Habenicht, Andreas J. R.; Mohanta, Sarajo K. (Frontiers in Immunology, 2019)
Vascular smooth muscle cells (VSMCs) constitute the major cells in the media layer of arteries, and are critical to maintain the integrity of the arterial wall. They participate in arterial wall remodeling, and play important roles in atherosclerosis throughout all stages of the disease. Studies demonstrate that VSMCs can adopt numerous phenotypes depending on inputs from endothelial cells (ECs) of the intima, resident cells of the adventitia, circulating immune cells, hormones, and plasma lipoproteins. This plasticity allows them to perform multiple tasks in physiology and disease. In this minireview, we focus on a previously underappreciated activity of VSMCs, i.e. their impact on atherosclerosis immunity via formation of artery tertiary lymphoid organs (ATLOs).